Needs and skills of informal caregivers to care for a dependent person: a crosssectional study - Dixe, Maria dos Anjos (2019)
The world is facing many socio-demographic changes, such as an increased average life expectancy and the presence of chronic and non-communicable diseases, which in turn, leads to an enhanced dependency on others. Consequently, the demand for informal caregivers has significantly increased during the past few years. Caring for a dependent person is linked to a series of burdens that often leads to physical, psychological and emotional difficulties. Taking into consideration the difficulties faced by informal caregivers, knowing in which areas of functioning they need more guidance may help to relieve their burden. Therefore, the main goal of this study is to better understand the needs and competencies of the informal caregiver when caring for a dependent person in the different self-care domains.